Lactobacillus rhamnosus GG modulates innate signaling pathway and cytokine responses to rotavirus vaccine in intestinal mononuclear cells of gnotobiotic pigs transplanted with human gut microbiota. Issue 1 (December 2016) - Wang, Haifeng; Gao, Kan; Wen, Ke; Allen, Irving; Li, Guohua; Zhang, Wenming; Kocher, Jacob; Yang, Xingdong; Giri-Rachman, Ernawati; Li, Guan-Hong; Clark-Deener, Sherrie; Yuan, Lijuan
Abstract Background A better understanding of mechanisms underlying dose-effects of probiotics in their applications as treatments of intestinal infectious or inflammatory diseases and as vaccine adjuvant is needed. In this study, we evaluated the modulatory effects ofLactobacillus rhamnosus GG (LGG) on transplanted human gut microbiota (HGM) and on small intestinal immune cell signaling pathways in gnotobiotic pigs vaccinated with an oral attenuated human rotavirus (AttHRV) vaccine. Results Neonatal HGM transplanted pigs were given two doses of AttHRV on 5 and 15 days of age and were divided into three groups: none-LGG (AttHRV), 9-doses LGG (AttHRV + LGG9X), and 14-doses LGG (AttHRV + LGG14X) (n = 3–4). At post-AttHRV-inoculation day 28, all pigs were euthanized and intestinal contents and ileal tissue and mononuclear cells (MNC) were collected. AttHRV + LGG14X pigs had significantly increased LGG titers in the large intestinal contents and shifted structure of the microbiota as indicated by the formation of a cluster that is separated from the cluster formed by the AttHRV and AttHRV + LGG9X pigs. The increase in LGG titers concurred with significantly increased ileal HRV-specific IFN-γ producing T cell responses to the AttHRV vaccine reported in our previous publication, suggesting pro-Th1 adjuvant effects of the LGG. Both 9- and 14-doses LGG fed pig groups had significantly higher IkBα level and p-p38/p38 ratio, while significantly lower p-ERK/ERK ratio than the AttHRV pigs, suggesting activation of regulatory signals during immune activation. However, 9-doses, but not 14-doses LGG fed pigs had enhanced IL-6, IL-10, TNF-α, TLR9 mRNA levels, and p38 MAPK and ERK expressions in ileal MNC. Increased TLR9 mRNA was in parallel with higher mRNA levels of cytokines, p-NF-kB and higher p-p38/p38 ratio in MNC of the AttHRV + LGG9X pigs. Conclusions The relationship between modulation of gut microbiota and regulation of host immunity by different doses of probiotics is complex. LGG exerted divergent dose-dependent effects on the intestinal immune cell signaling pathway responses, with 9-doses LGG being more effective in activating the innate immunostimulating TLR9 signaling pathway than 14-doses in the HGM pigs vaccinated with AttHRV.